The Effect of Using Role, Audience, Format, Topic (R.A.F.T) Strategy on Students’ Ability Writing Greeting Card at Ninth Grade of SMP Jami’iyyatul Hujjaj Bukittinggi - Novianti, Rahmi; Safitri, Loli; Sakti, Genta; Syahrul, Syahrul (Education Achievement: Journal of Science and Research, 2024)
This research looked at how the RAFT technique affected the ninth-grade pupils at SMP Jam'iyyatul Hujjaj's capacity to write greeting cards. The research was motivated by the pupils' struggles with writing in their English language studies. This study used a pre-experimental design with a single group undergoing both pre- and post-test design classes. The 26 students enrolled in the ninth grade at SMP Jam'iyyatul Hujjaj Bukittinggi made up the research population. The sample utilized in this study was obtained using complete sampling. Writing tests served as the research tool in this study. The paired sample t-test in SPSS 22 was used to evaluate the data. According to the research's findings, there was a noticeable difference in students' capacity to write greeting cards between classes that used the RAFT technique and those who did not. As can be seen, the result obtained (5.451>2.060) is greater than the value in the table. Based on the statistics, it can be inferred that the RAFT technique significantly improved the writer's capacity to write greeting cards.